Comparative analysis of mitochondria surrounding the intercalated discs in heart diseases: an ultrastructural pilot study - Schönmehl, Rebecca; Mendelsohn, Daniel H.; Winter, Lina; Pabel, Steffen; Niedermair, Tanja; Evert, Katja; Cheung, Wing-Hoi; Wong, Ronald Man Yeung; Schmitt, Volker H.; Keller, Karsten; Barsch, Friedrich; Dietl, Alexander; et al. (International journal of molecular sciences, 2024)
Background: Mitochondria play a crucial role in adapting to fluctuating energy demands, particularly in various heart diseases. This study investigates mitochondrial morphology near intercalated discs in left ventricular (LV) heart tissues, comparing samples from patients with sinus rhythm (SR), atrial fibrillation (AF), dilated cardiomyopathy (DCM), and ischemic cardiomyopathy (ICM). Methods: Transmission electron microscopy was used to analyze mitochondria within 0-3.5 μm and 3.5-7 μm of intercalated discs in 9 SR, 10 AF, 9 DCM, and 8 ICM patient samples. Parameters included mean size in µm2 and elongation, count, percental mitochondrial area in the measuring frame, and a conglomeration score. Results: AF patients exhibited higher counts of small mitochondria in the LV myocardium, resembling SR. DCM and ICM groups had fewer, larger, and often hydropic mitochondria. Accumulation rates and percental mitochondrial area were similar across groups. Significant positive correlations existed between other defects/size and hydropic mitochondria and between count/area and conglomeration score, while negative correlations between count and size/other defects and between hydropic mitochondria and count could be seen as well. Conclusion: Mitochondrial parameters in the LV myocardium of AF patients were similar to those of SR patients, while DCM and ICM displayed distinct changes, including a decrease in number, an increase in size, and compromised mitochondrial morphology. Further research is needed to fully elucidate the pathophysiological role of mitochondrial morphology in different heart diseases, providing deeper insights into potential therapeutic targets and interventions.
Gesehen am 06.02.2025